VD_FINDINFO Jug / 2014 / 297 vom 2. Mai 2014 - VD Tribunal cantonal (2014)
COURTAGE, SÉQUESTRELP, DOMMAGES-INTÉRÊTS, TORT MORAL, NOUVEAU MOYEN DE FAIT | 412 CO, 415 CO, 49 al. 1 CO, 284 al. 2 CPC, 273 al. 1 LP